Impact of different foot arches on standing balance and physical performance among nursing students / Nur Farhana Md Yunus, Noor Shazana Zainal and Ummu Tsara Mustafa - Md Yunus, Nur Farhana; Zainal, Noor Shazana; Mustafa, Ummu Tsara (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
Foot arches were classified into normal, high and low arches. Abnormal foot arches has been reportedly high prevalent among young adult population. Balance and physical performance are considered important elements among nursing students especially during clinical which primarily involved prolonged weight-bearing activities. This study aimed to identify different foot arches and to assess the impact of those foot arches on standing balance and physical performance among nursing students. This study was conducted among 80 nursing students, age between 18 to 25-year-old. Types of foot arch were identified using navicular drop test (NDT). Static balance was measured using the One-Legged Stance test (OLS) in eyes open (EO) and eyes closed (EC). Dynamic balance was measured using Star Excursion Balance Test (SEBT) in anterior (ANT), posterolateral (PL) and posteromedial (PM) direction while physical performance components were tested using Vertical Jump Test (VJT) and Edgren Side to Side Test (ESST). No significant differences in OLS in EO (p=0.608), EC (p=0.363) and SEBT ANT (p=0.704), PL (p=0.997), PM (p=0.088),VJT (p=0.626) and ESST (p=0.469) score among participants. Nursing students with normal, low and high arches were no impact in both standing balance and physical performance.